Determination of 11 Kinds of Organophosphorus Flame Retardants in Baby Rice Cereal by Ultra-high Performance Liquid Chromatography-tandem Mass Spectrometry - Xi WANG; Yingru LING; Hao ZHANG; Wenliang JI (Shipin gongye ke-ji, 2022)
A method for the determination of 11 organophosphorus flame retardants in baby rice flour was established by ultra performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). The samples were extracted by 0.5% formic acid acetonitrile solution by ultrasound. The extracted solution was purified by dispersive solid phase extraction packing and filtered by polytetrafluoroethylene membrane and detected by UPLC-MS/MS. Gradient elution was carried out with 5 mmol/L ammonium formate and acetonitrile. The target compounds were separated by ACQUITY UPLC® BEH C18 column (100 mm×2.1 mm, 1.7 μm), and multiple response monitoring (MRM) was conducted in the positive electrospray ionization mode. The external standard method was used for quantification. By optimizing chromatographic conditions, all the 11 kinds of organophosphorus flame retardants achieved baseline separation. The 11 kinds of organophosphorus flame retardants had a good linear relationship in the range of 0.5~100 μg/L (Tris (2-ethylhexyl) phosphate 0.05~10 μg/L) with correlation coefficient r>0.994. The limits of detection (3S/N) were 0.003~0.926 μg/kg and the limits of quantitation (10S/N) were 0.01~2.78 μg/kg. The average recoveries at three spiked levels (low, medium and high) were 63.2%~113.4% with the relative standard deviations all less than 10% (n=6). Four kinds of baby rice cereal were analyzed by the established method and the detection rate of triphenyl phosphate (TPhP) was up to 100%. Tributyl phosphate (TnBP) and tris (2-chloroisopropyl) phosphate (TCPP) were also detected in one of the samples. The method could be used for the determination of trace organophosphorus flame retardants in baby rice flour cereal with accurate and reliable results.